A New Species of Boiga Fitzinger, 1826 (Serpentes: Colubridae) from The Northern Western Ghats of India - Giri, Varad B.; Deepak, V.; Captain, Ashok; Pawar, Swapnil; Tillack, Frank (Journal of the Bombay Natural History Society (JBNHS), 2019)
A new species of colubrid snake of the genus Boiga Fitzinger, 1826 is described, based on three specimens. Boiga thackerayi sp. nov. is presently known only from its type locality from a hill stream near Koyna, Satara district in northern Western Ghats of peninsular India. A medium sized Boiga characterized by smooth dorsal scales arranged in 19/19-17/15 rows, ventrals 211-221; subcaudals 93-101, dorsum with indistinct bands and belly distinctly marked. This is the second species of Boiga after B. dightoni that is endemic to the Western Ghats and the first new species of Boiga described after 125 years from the Western Ghats. The molecular data also proved the distinctiveness of this species from its congeners from India and Sri Lanka, which was supported by a limited but precise set of morphological variations. This is apparently the first known species of Boiga which feeds on frog eggs.